Employment protection and fertility: Evidence from the 1990 Italian reform - Ervin Prifti; Daniela Vuri (Institute for the Study of Labor (IZA), 2012)
The aim of this paper is to investigate the effect of Employment Protection Legislation (EPL) on fertility decisions of Italian working women using administrative data. We exploit a reform that introduced in 1990 costs for dismissals unmotivated by a 'fair cause' or 'justified motive' in firms below 15 employees and left firing costs unchanged for bigger firms. We use this quasi-experimental setup to study the hypothesis that increased EPL reduces future job insecurity and positively affects a female worker's proneness to take childbearing decisions. We use a difference in difference (OLS-DID) model to control for possible period-invariant sorting bias and an instrumental variable (IV-DID) model to account for time-varying endogeneity of the treatment status. We find that reduced economic insecurity following a strengthening of the EPL regime has a positive and sizable effect on fertility decisions of Italian working women. This result is robust to a number of checks regarding possible interactions with other policy reforms occurring around 1990, changes in the sample of workers and firms, and use of an alternative set of exclusion restrictions.
Keywords: J2; J13; J65; 330; fertility; employment protection; difference-in-difference; instrumental variables; policy evaluations; Arbeitnehmerschutz; Wirkungsanalyse; Weibliche Arbeitskräfte; Arbeitsplatzsicherung; Fruchtbarkeit; Italien